Spatial and temporal trends of perfluoroalkyl acids in water bodies: A case study in Taihu Lake, China (2009–2021). (15th January 2022) - Yu, Liang; Liu, Xiaodong; Hua, Zulin; Zhang, Yuan; Xue, Hongqin
Abstract: Perfluoroalkyl acids (PFAAs) have been ubiquitously detected in water bodies and are a cause of great public concern due to their adverse effects. This study investigated the long-term temporal-spatial trends of PFAAs in the water bodies of the entire Taihu Lake, and predicted PFAA concentrations for 2024. A field investigation conducted in 2021 and previous data allowed to derive trends over a broad temporal-spatial scale, which is often not feasible in short-term studies. In the 2009–2021 period, the most quantifiable PFAAs increased, among which perfluorooctanoic acid and perfluorohexanoic acid were predominant. As of 2021, the mean total concentration of ten PFAAs (∑10 PFAA) showed a distinct spatial decreasing trend, moving from north to south within the lake, and similar spatial distribution patterns were also noted in other years. The main PFAA input and most serious contamination were concentrated in the northern region, due to the riverine inputs and clustering of PFAA-related industries. The ∑10 PFAA concentration in the wet season was greater and presented a more uniform distribution pattern than that in the dry season, possibly due to the combined effects of the degradation of PFAA precursors, water inflow, rainfall, shipping activities, and a shallow water column. From 2009 to 2021 the ∑10 PFAA concentration of the entire lake showed an increasing trend, but the rate of increase was significantly reduced. In addition, a grey model predicted that the mean ∑10 PFAA concentration in the entire Taihu Lake will reach 431 ng/L in 2024, and the northern region will be affected by a more serious PFAA pollution in the future because it exhibited a high mean ∑10 PFAA concentration of 426 ng/L in 2021. These findings provide novel insights into the temporal-spatial distribution of PFAAs in Taihu Lake, and could help regulators to formulate policy decisions in response to PFAA pollution. Graphical abstract: Image 1 Highlights: The temporal-spatial variations of PFAAs in Taihu Lake were investigated. High PFAA concentrations were founded in northern region of Taihu Lake. PFAA level in wet season was greater, presenting uniform distribution pattern. Though PFAAs were increasing in the lake the rate is significantly decreasing. PFAA concentration in 2024 was predicted to reach 431 ng/L.